2018
DOI: 10.14254/2071-789x.2018/11-2/22
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Lean Methods in Central Eastern European Countries: the Case of Czech and Slovak Republic

Abstract: Increasing competition, both at the global and local levels, shortening product life cycle, and strengthening customer's position are only some of the factors currently affecting the viability of businesses. To stay at a market, retain old and gain new customers businesses are constantly looking for new ways to improve. One of the possibilities to improve is the lean concept. This concept offers the ways to find the points with waste and eliminate them. The main objective of this research is to analyze the ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Adoption of TPM can help to ensure the competitiveness of a company because maintenance is the area with great potential to be used as a competitive advantage (Mwanza & Mbohwa, 2015; Kalpande & Toke, 2022); it is one approach used to make business more competitive (Pinto et al, 2020). Gálová et al (2018) and Rajnoha et al (2018) found that approximately 21% of industrial companies in the Czech Republic use the TPM methodology in their practice. Gálová et al (2018) add that TPM is primarily used in the automotive (45%), followed by the electro-technics (22%), wood processing (20%), and mechanical (14%) industries.…”
Section: Total Productive Maintenancementioning
confidence: 99%
See 1 more Smart Citation
“…Adoption of TPM can help to ensure the competitiveness of a company because maintenance is the area with great potential to be used as a competitive advantage (Mwanza & Mbohwa, 2015; Kalpande & Toke, 2022); it is one approach used to make business more competitive (Pinto et al, 2020). Gálová et al (2018) and Rajnoha et al (2018) found that approximately 21% of industrial companies in the Czech Republic use the TPM methodology in their practice. Gálová et al (2018) add that TPM is primarily used in the automotive (45%), followed by the electro-technics (22%), wood processing (20%), and mechanical (14%) industries.…”
Section: Total Productive Maintenancementioning
confidence: 99%
“…Gálová et al (2018) andRajnoha et al (2018), who have found that approximately 21% of companies in the Czech Republic use TPM in their practice. However, On the other hand, TPM is more complex and, in terms of implementation, a bit more demanding than SMED; therefore, it is possible to perceive these findings more positively compared to SMED.…”
mentioning
confidence: 99%